The nine development bands: A conceptual framework and global theory for waste and development. Issue 10 (October 2021) - Whiteman, Andrew; Webster, Mike; Wilson, David C
Solid waste management (SWM) is an essential utility service. More than two to three billion people worldwide still lack basic services, whereas some countries are already moving beyond SWM towards waste and resource management (WaRM) and a circular economy. This paper sets out a novel conceptual framework and global theory of waste and development, providing a road map, allowing a country or city to locate their current position and plot their way ahead. We identify nine development bands (9DBs) with significant commonalities in terms of critical challenges and developmental pressure points. DB1–DB4 reflect stepwise improvement towards the new baseline of meeting the SDG 11.6.1 indicators of universal collection and management in controlled facilities (DB5). Countries can then choose to move towards environmentally sound management and the 'reduce, reuse, recycle' (3Rs) (DB6-9), with an ultimate aspiration of 'zero waste'. We test the 9DBs conceptual framework against historical journeys of higher income countries. The main application will be in low- and middle-income countries striving towards SDG 11.6.1, where it fills a key gap in the practitioners' toolkit by enabling initial framing/scoping of the problem and smarter interventions to be designed and sense checked. Key insights include targeted governance/institutional reforms, appropriate and affordable systems/technology and adapting solutions to a diversity of local needs and realities.